Casein phosphopeptides drastically increase the secretion of extracellular proteins in Aspergillus awamori. Proteomics studies reveal changes in the secretory pathway - Kosalková, Katarina; García-Estrada, Carlos; Barreiro, Carlos; Flórez, Martha G; Jami, Mohammad S; Paniagua, Miguel A; Martín, Juan F (Microbial cell factories, 2012)
The secretion of heterologous animal proteins in filamentous fungi is usually limited by bottlenecks in the vesicle-mediated secretory pathway. Using the secretion of bovine chymosin in Aspergillus awamori as a model, we found a drastic increase (40 to 80-fold) in cells grown with casein or casein phosphopeptides (CPPs). CPPs are rich in phosphoserine, but phosphoserine itself did not increase the secretion of chymosin. The stimulatory effect is reduced about 50% using partially dephosphorylated casein and is not exerted by casamino acids. The phosphopeptides effect was not exerted at transcriptional level, but instead, it was clearly observed on the secretion of chymosin by immunodetection analysis. Proteomics studies revealed very interesting metabolic changes in response to phosphopeptides supplementation. The oxidative metabolism was reduced, since enzymes involved in fermentative processes were overrepresented. An oxygen-binding hemoglobin-like protein was overrepresented in the proteome following phosphopeptides addition. Most interestingly, the intracellular pre-protein enzymes, including pre-prochymosin, were depleted (most of them are underrepresented in the intracellular proteome after the addition of CPPs), whereas the extracellular mature form of several of these secretable proteins and cell-wall biosynthetic enzymes was greatly overrepresented in the secretome of phosphopeptides-supplemented cells. Another important 'moonlighting' protein (glyceraldehyde-3-phosphate dehydrogenase), which has been described to have vesicle fusogenic and cytoskeleton formation modulating activities, was clearly overrepresented in phosphopeptides-supplemented cells. In summary, CPPs cause the reprogramming of cellular metabolism, which leads to massive secretion of extracellular proteins.